Measuring exception handling in software system - Luo, Yan. (2008)
The exception handling, which conventionally refers to an automatic replacement of a standard program execution by an exceptional execution when an occurrence of exception is detected by the program, is critically important for program reliability and robustness. Measuring the quality of exception handling provision can generate quantitative descriptions of the provision, enable us to select better techniques and tools to control and improve the exception handling features. In this project, a metric suite is proposed to measure some exception handling features, i.e. integrality and recoverability in error-correction for a transaction, error-handling capability for a transaction and for a system. The experimentation of the metric suite is carried out for three industrial applications using empirical analysis. The experimentation is based on the available software deliverables such as code and system documentation. We also perform a validation for the proposed metric suite.